Long noncoding RNA GAS5 and miR-137 and two of their genetic polymorphisms contribute to acute ischemic stroke risk in an Egyptian population - Doaa Taha.Ahmed Elsabagh; Olfat Gamil Shaker; Hanan. Helmy Elgendy; Marwa Mohammad Mona; Amul Mohammad.Abd ElRahim Badr (Journal of the Pakistan Medical Association, 2023)
Objectives: To assess the serum expression levels of long non-coding ribonucleic acid growth arrest specific-5 and micro-ribonucleic acid-137, and the different genotypes of long non-coding ribonucleic acid growth arrest specific-5 rs2067079 (C>T) and micro-ribonucleic acid-137 rs1625579 (T>G) in acute ischaemic stroke patients. Methods: The case-control study was conducted at Cairo University, Cairo, Egypt, from January to August 2020, and comprised adult acute ischaemic stroke patients of either gender selected from the stroke unit of the Neurology Department at Kasr Alainy Hospital of Cairo University. Healthy individuals matched for age and gender were enrolled as controls. Quantitative real-time polymerase chain reaction was used to quantify serum expression levels of long non-coding ribonucleic acid growth arrest specific-5 and micro-ribonucleic acid-137, and to genotype long noncoding ribonucleic acid lncRNA growth arrest specific-5 rs2067079 and micro-ribonucleic acid-137 rs1625579 using TaqMan allelic discrimination. Data was analysed using SPSS 22. Results: Of the 100 subjects, 50(50%) were patients; 34(68%) males and 16(32%) females with mean age 60.4±10.0 years. The remaining 50(50%) were controls; 28(56%) males and 22(44%) females with mean age 56.9±12.2 years (p>0.05). The patients had more smokers, more hypertensives and more diabetics than the controls (p<0.05). Long non-coding ribonucleic acid growth arrest specific-5 expression levels were significantly increased, while microribonucleic acid-137 expression levels were significantly reduced among the patients (p<0.05). Acute ischaemic stroke risk was significantly higher in patients with growth arrest specific-5 rs2067079 (C>T) recessive model (homozygous minor TT genotype), while micro-ribonucleic acid-137 rs1625579 (T>G) was protective against acute ischaemic stroke in allelic (G minor allele), codominant (GT genotype), dominant (GT+GG), and over-dominant (GT genotype) models (p<0.05). Conclusion: Long non-coding ribonucleic acid growth arrest specific-5 rs2067079 and micro-ribonucleic acid-137 rs1625579 may act as novel genetic markers of acute ischaemic stroke risk. Keywords: RNA, Polymorphism, Nucleotide, Alleles, Genetic, Ischemic stroke, Transcriptase polymerase, MicroRNAs, Genotype.